2012
DOI: 10.1371/journal.pcbi.1002659
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics on Protein Bi-stability Landscapes can Potentially Resolve Adaptive Conflicts

Abstract: Experimental studies have shown that some proteins exist in two alternative native-state conformations. It has been proposed that such bi-stable proteins can potentially function as evolutionary bridges at the interface between two neutral networks of protein sequences that fold uniquely into the two different native conformations. Under adaptive conflict scenarios, bi-stable proteins may be of particular advantage if they simultaneously provide two beneficial biological functions. However, computational model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 98 publications
2
47
2
Order By: Relevance
“…For the G A /G B system, a mutationinduced gradual stabilization of one structure over another was demonstrated using a common software for DDG prediction ( §2.1) [178]. However, the mutation-induced G A /G B conformational switching was not reproduced in atomistic molecular dynamics simulations [67], even though a part of the simulated energetics is consistent with experiment [68].…”
Section: Bi-stable Proteins and Conformational Switchesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the G A /G B system, a mutationinduced gradual stabilization of one structure over another was demonstrated using a common software for DDG prediction ( §2.1) [178]. However, the mutation-induced G A /G B conformational switching was not reproduced in atomistic molecular dynamics simulations [67], even though a part of the simulated energetics is consistent with experiment [68].…”
Section: Bi-stable Proteins and Conformational Switchesmentioning
confidence: 99%
“…However, it can also be argued that evolution of certain IDPs/IDRs may be subject to even more restrictive constraints because of their requirement to bind to multiple partners. As a result, these IDP/IDRs may suffer from low mutational robustness similar to that of bi-stable globular proteins that play the role of an evolutionary bridge between two folded structures [178,239]. Nevertheless, even in such cases, IDPs/IDRs in a neutral net might only need to conserve certain functional residues that are compatible with multiple binding partners while imposing few constraints on mutations at amino acid sites in the rest of the protein.…”
Section: Biophysical Constraints On Evolution Of Intrinsically Disordmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In general, however, it may be more common for bridge sequences to have lower native state stability than sequences with a single native structure. 23 …”
Section: Overlap Of Multiple Stable Folds In Sequence Spacementioning
confidence: 99%
“…14 Limited mutagenesis of small natural proteins populates alternate folds in certain cases, [15][16][17] and accumulation of simple mutations can lead to evolution of new folds. [17][18][19] Some modeling studies have found numerous close approaches or paths between different structures in sequence space [20][21][22][23] and even sequence ''supernetworks'' 24,25 that span many protein folds. In addition, sequences with two folds or functions may confer a fitness advantage under certain models of adaptive evolution.…”
Section: Introductionmentioning
confidence: 99%